Hybrid coronary revascularization versus percutaneous strategies in left main stenosis: a propensity match study. Issue 5 (May 2018) - Repossini, Alberto; Di Bacco, Lorenzo; Rosati, Fabrizio; Tespili, Maurizio; Saino, Antonio; Ielasi, Alfonso; Muneretto, Claudio
Abstract : Aims: Hybrid revascularization (HCR) has been recently proposed as an alternative strategy in multivessel coronary disease, particularly in patients with high SYNTAX scores and risk scores. The objective of this study is to evaluate the outcomes of HCR versus percutaneous coronary intervention (PCI) drug-eluting stenting in left main treatment. Methods: A series of 198 consecutive patients with left main stenosis have been treated. HCR, was performed in 77 patients (G1) whereas 121 patients (G2) received PCI on left main. An adjusted analysis using inverse probability weighting (IPW) was performed. Primary outcomes include: 30-day mortality, postoperative acute myocardial infarction, 18 months' MACCEs: cardiac death, stroke, acute myocardial infarction (AMI), repeated target vessel revascularization (TVR). Results: SYNTAX score was 29.5 ± 6.9 in G1 and 29.1 ± 6.5 in G2 ( P  = 0.529). In G2, three patients (2.7%) died because of cardiogenic shock; no deaths occurred in G1 ( P  = 0.603). No major complications were reported in G1 and there was no mortality at 18 months' follow-up in both groups. Survival freedom from MACCEs at 18 months' follow-up was significantly higher in G1 (G1: 93.3 ± 4.6% versus G2: 72.3 ± 6.3; P  = 0.001) mostly because of the higher freedom from TVR (G1: 93.3 ± 4.6% versus G2: 75.5 ± 5.6; P  = 0.002). At Cox regression analysis, PCI was an independent predictor of MACCEs and TVR (hazard ratio 3.9, CI 1.36–9.6; P  = 0.027). Conclusion: PCI in patients with left main and multivessel disease is a viable strategy, with a good outcome. HCR, demonstrated a lower incidence of cardiac adverse events such as AMI and TVR. Future comparative studies will be helpful to identify the optimal patient population for HCR.